Miopia Tinggi pada Kehamilan : Case Report - Basoeki , Rijanto Agoeng; Ramadhani , Devi Eka; Tarina, Nadia; Aisyah , Nabilla Nur (JurnalMU: Jurnal Medis Umum, 2025)
Background: High Myopia (HM), defined as a myopic refractive error of ≥6 diopters (D) or an axial length (AL) greater than 26.5 mm, is associated with various typical pathological changes, such as fundus tessellation, conus, macular lesions, as well as peripheral retinal and choroidal lesions. The choroid and retina are thought to be vulnerable to the effects of pregnancy. HM is associated with retinal changes, and patients with HM have a high risk of experiencing retinal detachment. Objective : This case report aims to describe high myopia in pregnancy. Case Presentation : A 23-year- old woman, GIP00000, at 37 weeks of gestation, came to the emergency department of Dr. Soegiri Lamongan General Hospital with complaints of intense abdominal tightness and swollen, painful feet. Her vision appeared blurred. High blood pressure was noted in the third trimester. An obstetric examination showed that the fetal head had not entered the pelvic inlet. Clinical symptoms included blurred vision, with visual acuity results of VOD -8.00 D and VOS -8.00 D. Conclusion : High myopia in pregnancy is a rare case. Diagnosis is based on patient history, clinical symptoms, and supportive examinations. High myopia is not a contraindication for normal delivery. However, high myopia poses a significant risk during pregnancy, which was considered as a basis for a cesarean section to reduce risks in our case. Keywords : Myopia, pregnancy, High Myopia in Pregnancy, retinal detachment.